An evaluation of the transformation of public service delivery through the development of administrative justice in South Africa - Monyakane, Mampolokeng Mathuso Mary-Elizabeth (Stellenbosch : University of Stellenbosch, 2008)
Thesis (LLM (Public Law))--University of Stellenbosch, 2007.